EFFECT OF ARBUSCULAR MYCORRHIZAL COLONIZATION ON EARLY GROWTH AND NUTRIENT CONTENT OF TWO PEAT SWAMP FOREST TREE SPECIES SEEDLINGS, Calophyllum hosei AND Ploiarium alternifolium - Turjaman, Maman; Santoso, Erdy; Tamai, Yutaka; Osaki, Mitsuru; Tawaraya, Keitaro (Indonesian Journal of Forestry Research, 2006)
Tropical peat-swamp forests are one of  the largest near-surface reserves of terrestrial organic carbon,  but rnany peat-swamp forest tree species decreased due over-exploitation, forest fire and conversion of natural forests into agricultural lands. Among those species are slow-growing Calophyllum  hoseiand Ploiarium  alternifolium, two species are good for construction of boats, furniture, house building and considerable attention from pharmacological viewpoint for human healthly. This study was aimed at understanding the effects of arbuscular mycorrhizal (AM) fungi on early growth of  C. hosei and P.alternifoliumunder greenhouse condition. Seedlings of C. hosei and P.alternifoliumwere inoculated with AM fungi: Glomus clarum and Glomus aggregatum ,or uninoculated under greenhouse condition during 6 months. AM colonization,   plant growth,  survival rate and  nutrient  content  (P, Zn  and B) were measured. The percentage of C. hoseiand P.alternifolium ranged from 27-32% and 18-19%,  respectively. Both inoculated seedling species had greater plant  height, diameter, leaf number, shoot and root dry weight than control  seedlings.   Nutrient  content  of  inoculated  plants  were increased with AM colonization- Survival rates of  inoculated plants were higher (100%)  than those of  control plants (67%). The results suggested that inoculation of AM fungi could improve the early growth of C. hoseiand P.alternifolium grown in tropical peat-swamp forest therefore  this finding has greater potential impact if this innovative technology applied in field scales which are socially acceptable, commercially profitable and environmentally friendly.